The Effect of Red Ginger Compress on Joint Pain in the Elderly - Setyobudi, Yustina Emi; Syukkur, Achmad; Dwi Astutik, Nanik (Babali Nursing Research, 2024)
Background : Elderly people will experience physical, social, and psychosocial changes. One of the complaints resulting from physical changes in the elderly is joint pain. Joint pain in the extremities experienced by the elderly is one of the most prevalent. Pain therapy using non-pharmacological techniques is an effective pain treatment and has minimal side effects for the elderly. One non-pharmacological technique that can be used to reduce pain in the elderly is using a red ginger compress. The content of red ginger can help reduce pain and act as an anti-inflammatory. Methods: Using a purposive sampling technique, 70 respondents were involved in this research. The group was divided into 2, namely 35 respondents as the control group and 35 respondents as the intervention group. Results : the results of the multivariate analysis test of a simple linear regression test showed that there was an effect of simultaneously administering red ginger compresses with a p-value of 0.000. Conclusion : Providing red ginger compress intervention has obtained significant results or has an effect on pain in the elderly, it is hoped that the elderly can take advantage of this intervention to reduce the symptoms and impact of musculoskeletal pain.